Financing constraints and risk management: Evidence from micro-level insurance data - Emil Bustos; Oliver Engist; Gustav Martinsson; Christian Thomann (Research Institute of Industrial Economics (IFN), 2022)
We study the impact of financing constraints on corporate risk management. Using data on credit scores matched with unique information on firm level commercial insurance purchases, we find that financing constraints lead to higher insurance spending. We adopt a regression discontinuity design and show that financially constrained firms spend 5-14% more on insurance than otherwise similar unconstrained firms. Our findings add new insights to the longstanding empirical puzzle whether financially constrained firms engage more in risk management. Furthermore, our results, shed light on risk management in smaller, mostly private firms.
Keywords: D22; D25; G22; G32; 330; Financing Constraints; Risk Management; Insurance Demand; Credit Scores; Private Firms